Faktor-faktor yang Memengaruhi Niat Wisatawan Asal Batam untuk Berwisata ke Malaysia - Erika; Renza Fahlevi; Fitriana Aidnila Sinambela (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2026)
This research aims to identify and analyze the factors influencing the intention of tourists from Batam to visit Malaysia. The main issue addressed is the limited understanding of the factors that drive tourists from Batam to choose Malaysia as their destination, despite its geographical proximity and the tourism potential that has not been fully explored. This study employs an explanatory quantitative approach, with a total sample of 282 respondent collected using convenience sampling and purposive sampling. Data were analyzed using Smart PLS 3.0 and IBM SPSS Statistics 27. The findings reveal that perceived value and experience quality have a significant positive impact on tourist satisfaction. Additionally, perceived value and experience quality have a significant positive effect on revisit intention. Nevertheless, perceived value and experience quality positively influence revisit intention when mediated by tourist satisfaction. For future research, it is recommended to explore additional factors such as nostalgia, authenticity, social media and perceived risk on tourist decisions-making. A comparative analysis between the experiences of domestic and international tourists is also suggested. This study is expected to contribute to Malaysia's tourism industry by enhancing tourism revenue through improved services and innovative developments.